Solid-phase extraction of organic dyes on mixed-ligand Zr(IV) metal–organic framework - Kharisov, Boris I.; Kharissova, Oxana Vasilievna; Zhinzhilo, Vladimir; Bryantseva, Julia; Uflyand, Igor (Multidisciplinary Digital Publishing Institute, 2022)
Currently, among the various areas of targeted wastewater treatment, great attention is being given by researchers to the solid-phase extraction of organic dyes using metal–organic frameworks (MOFs). In this work, a mixed-ligand Zr-MOF containing terephthalic acid and 1,10- phenanthroline as linkers was used for this purpose. The limiting adsorption of the dyes Congo red and methylene blue, according to experimental data, is 40 mg/g. The influence of various parameters (time, temperature, adsorbent dosage, pH, and coexisting ions) on adsorption characteristics was studied. The sorbent was tested for the removal of dyes from drinks in water and in artificial seawater. The possibility of the separation of dyes by column chromatography using a sorbent as a filler was studied.